Época de semeadura, regimes de corte, produção e qualidade de sementes de milheto - Coimbra, Rogério De Andrade [UNESP]; Nakagawa, João (Associação Brasileira de Tecnologia de Sementes, 2006)
Pearl millet is a tropical annual grass, used for animal feeding as forage, in direct pasture, for cutting, hay, silage and grain crop for ration. The objective of the present study was the investigation of the behavior of millet, after different cutting systems, sown at two times, to verify the possibility of cultivation under the conditions in Botucatu-SP, 815 meters altitude, 22°50'59''S e 48°25'54''W, for seed production, as a crop in succession/rotation with another wet season crop. The experiment was carried out in pots, under a plastic tunnel, in a complete randomized block design, with two sowing times (April and September), each one with five treatments: T1) free growth, without cutting; T2) a cut when the plant reached 50 to 70cm height; T3) cutting when the plant reached flowering; T4) sequence of three cuttings when the plant reached 50 to 70cm height; T5) sequence of two cuttings when the plant reached flowering, and five replications. The variables evaluated were seed production, the component seed production per plant and the physical and physiological quality of the seeds. The data were submitted to the joint analysis of the sowing times and the averages were compared by the Tukey test at 5% significance. The results showed that sowing time and the cutting system affected the millet seed production and the quality. Sowing in April with at most one cutting in the vegetative phase was shown to be the best combination for the production of pearl millet seeds in Botucatu.

O milheto é uma gramínea anual, de clima tropical, empregada na alimentação animal como forrageira, em pastejo direto, para corte, feno, silagem e colheita de grãos para ração. O presente trabalho teve o objetivo de estudar o comportamento do milheto, após diferentes regimes de corte, semeado em duas épocas, para verificar a possibilidade de cultivá-lo em condições de Botucatu, 815 metros de altitude, 22°50'59''S e 48°25'54''O, visando a produção de sementes, como cultura em sucessão/rotação com outra de cultivo das águas. O experimento foi conduzido em vaso, sob túnel plástico, em delineamento de blocos ao acaso, com duas épocas de semeadura (abril e setembro), cada uma com cinco tratamentos: T1) crescimento livre, sem cortes; T2) um corte quando a planta atingiu 50 a 70cm de altura; T3) um corte quando a planta atingiu o florescimento; T4) seqüência de três cortes quando a planta atingiu 50 a 70cm de altura; T5) seqüência de dois cortes quando a planta atingiu o florescimento, e cinco repetições. Foram avaliados a produção de sementes, os componentes de produção de sementes por planta, e a qualidade física e fisiológica das sementes. Os dados foram submetidos à análise estatística através da análise conjunta das épocas de semeadura e as médias comparadas pelo teste de Tukey a 5% de significância. Os resultados apontam que a época de semeadura e o regime de corte afetam a produção e a qualidade das sementes de milheto. A semeadura em abril com no máximo um corte na fase vegetativa mostrou ser a melhor combinação para a produção de sementes de milheto em Botucatu.
Sowing time, cutting system, production and quality of pearl millet seeds
Keywords: Pennisetum americanum; cut system; germination; vigor; Pennisetum americanum; manejo de corte; germinação; vigor